Performance of different fungicides against multiple diseases of rice - and R.K. GOEL, J.S. LORE, T.S. THIND*, M.S. HUNJAN (Indian Phytopathology, 2007)
Efficacy of eight fungicides namely Tilt 25EC (propiconazole), Bavistin 50 WP (carbendazim), Baycor 25 WP (bitertanol), Contaf 5EC (hexaconazole), Dithane Z-78 (Zineb), Kitazin 48 EC (iprobenphos ), Saaf 75 WP (carbendazim -mancozeb), and Rhizocin 3L (validamycin) was compared against three economically important diseases of rice namely sheath blight (Rhizoctonia solam), sheath rot (Fusarium moniliforme) and brown spot (Drechslera oryzae), under laboratory and field conditions by artificial inoculation technique during kharif seasons 2002, 2003 and 2004. Tilt 25 EC @0.1% was found to be the most effective fungicide against the three diseases, where the lowest mean disease severity was 15.7% for sheath blight, 6.7% for sheath rot and 9.0% for brown spot, as compared to 51.4%, 24.8% and 48.5% in untreated checks of respective diseases. Second best fungicide appeared to be Bavistin 50 WP @ 0.1% that was also quite effective against sheath blight (18.1%) and sheath rot (10.5%) followed by Contaf 5EC @ 0.1%, but was least effective against brown spot (33.20%). Rhizocin 3 L @ 0.25% was also significantly effective against sheath blight. Baycor 25 WP@0.1% and Dithane Z-78 @ 0.25% were found to be least effective followed by Kitazin 48EC @ 0.2% and Saaf 75 WP @0.15% against the three diseases. Tilt 25 EC, was also found to be highly effective against grain discoloration followed by Bavistin 50 WP and Contaf 5 EC. Under laboratory conditions also Tilt 25EC demonstrated high level of efficacy followed by Contaf 5EC against the pathogens of above mentioned diseases. Bavistin 50WP was also equally effective against R. solani and F. moniliforme, but it did not check the growth of D. oryzae even at 200 ppm. Rhizocin 3L and Saaf 75WP also showed good activity, but Dithane Z-78 exhibited least activity against the test pathogens.